Dificuldades para a atualização de versão do sistema ERP R/3 da SAP: estudo de caso em empresa do segmento de bebidas - Valentim, Onivaldo Aparecido (Universidade Federal de São Carlos, 2010)
Many companies which adopted ERP systems in the past are frequently reluctant tostart new projects to upgrade the technology to newer versions. The decision is difficult due to thelong time of the project, the amount of financial investments and internal workforcerequired for the job, which are usually similar to the original ERP implementation. This work has asproposal a research and analisys of the apparently large demand of resources necessary to upgradethe versions of ERP R/3 systems. Firstly, a review in literature is made to present the arquitecture, characteristics and concepts of modules and funcionalities of these ERPs systems. It is alsoincluded the study of the life cicle of ERPs systems and its interfaces with legacy systems. Insequence, the versions upgrade subject is explored, where this author suggests that upgrade ofversions gives new life to ERPs systems and discuss how the suppliers share the ERP´s market andfinally explore the kinds of upgrades available for these systems. After these studies, twoquestionnaires are made to obtain data. This research is a Unique Case study type and has asobjective to describe the behavior of critic factors of implementation during an upgrade of ERPsystems, verifying if the demands are justified.
Keywords: Software - desenvolvimento; ERP - (Enterprise Resource Planning); SAP R/3 (Programa de computador); Fatores críticos de sucesso; Engenharia de produção; Atualização de versão; System s upgrade; ERP; Critics factors; ENGENHARIAS::ENGENHARIA DE PRODUCAO